Factors Related to Onset to Arrival Time in Acute Ischemic Stroke Patients Admitted into Nongkungsi Hospital, Karasin Province - Pookhao, Naphatsanan (Journal of Vongchavalitkul university, 2020)
Objectives: This Retrospective research aimed to study the prehospital time of patients after acute ischemic stroke symptoms and factors related to the prehospital time in patients after acute ischemic stroke symptoms in Nongkungsi Hospital. Methods: One hundred and two patients with acute ischemic stroke admitted in Nongkungsi Hospital were recruited. The instruments used for data collection were the demographic data form, knowledge about stroke, and the prehospital time of patients with acute ischemic stroke. Data were analyzed by using descriptive statistics and chi-square. Results: The study revealed that most of the patients were male (52.0%), average age at 64 years (S.D. = 11.62), education level below Primary School (56.9 %), had no-occupation (53.9%), traveled to hospital after acute ischemic stroke symptoms by personal and public car, not by Emergency Medical Service (82.3%), the average prehospital time after acute ischemic stroke symptoms was 22.4 hr., and prehospital time was longer than 270 minutes (51.96%). The study found that the knowledge and information about stroke had statistically significant relationship with prehospital time of patients after acute ischemic stroke symptoms at p <0.05. The results of this research suggests that the knowledge and information of stroke symptoms and symptom management should be provided to those people close to the patients who are at risk for stroke. So that the patients can get early access and receive proper treatments.